PENGARUH KEMAMPUAN KERJA TERHADAP KINERJA APARATUR SIPIL NEGARA (ASN) DI KANTOR CAMAT PADANG SELATAN KOTA PADANG - Eva Suryany; Siti Osa Kossasy; Fenny Ayu Monia; Juli Yes Derita Gulo (Jurnal Public Administration, Business and Rural Development Planning, 2019)
The purpose of this study is to 1) find out how the workability of the Civil Servant in the South Padang Sub-district office, 2) investigate how the performance of Civil Servant in the South Padang Sub-district Office. The research used is a Quantitative Research Method. The population is all employees of the Padang Selatan sub-district office of Padang city. Based on the results of the research CS workability level in the South Padang subdistrict office has so far reached 69.4%, the CS workability has reached a fairly good category with the level of respondents' achievements (TCR) between 65% - 79.99%, the results of ASN performance research in subdistrict office of South Padang so far have reached 71%, the CS performance has reached a fairly good category. The results of hypothesis testing can be explained that there is a strong relationship with interpretation between 0.60-0.799 and positive with a significant level smaller than 0.05 which is equal to 0,000. Based on the determinant coefficient test the Effect of Work Ability on CS Performance in the subdistrict office of South Padang is 62.6%, the remaining 37.4%. It is explained by other variables not included in the research model. Based on the results of a simple regression analysis, it was found that the workability variable has a positive and significant effect on the performance of the Civil Servant (CS) in subdistrict office of South Padang.